The assessment of psychometric properties of childbirth violence questionnaire in Iranian women - Molouk Jaafarpour; Ziba Taghizadeh; Abbas Ebadi; Fatemeh Abbaszadeh; Fatemeh Najafi; Ashraf Direkvand-Moghaddam (PLoS ONE, 2025)
Background Childbirth violence is a cultural and social issue with a complex and multidimensional nature that silently threatens women’s health around the world. Thus, designing an instrument based on social norms and the cultural context of society is an essential need. The study aims to develop and validate a measurement instrument that assesses childbirth violence, focusing on the experiences of women during childbirth. Methods The study utilized a mixed-methods approach which is a combination of qualitative and quantitative research methodologies and evaluated a new tool for assessing violence during childbirth. It included three main phases: Instrument Development, Validity, and Reliability. The instrument’s validity was tested through exploratory factor analysis (EFA). To assess sampling adequacy, the Kaiser-Meyer-Olkin index. Multiple extraction and rotation techniques were employed to determine the optimal questionnaire structure. Results After completing the qualitative phase, the research team focused on two key themes: the violation of pregnant mothers’ rights within the healthcare system and societal factors contributing to violence against pregnant mothers. 99 items were identified based on participants’ perspectives and interviews. Existing questionnaires on respectful maternal care were reviewed, but none specifically targeted childbirth violence. A comprehensive pool of 108 items was refined to a preliminary questionnaire with 65 items for psychometric testing. EFA, based on maximum likelihood and varimax rotation, concealed that questionnaire contains four factors including; psychological and physical abuse, non-professional care, delay in offering care and lack of family support. These factors explained 63.276% of the total variance. Cronbach’s alpha (0.88–0.90), (ICC = 0.95 (and (SEM = 3.2), confirmed the sufficient reliability of the Childbirth Violence Questionnaire with 34 items (CBVQ-34). Conclusions The CBVQ is a unique tool to assess childbirth violence through mothers’ experiences during natural birth or emergency cesarean sections. It focuses on violence from care teams, the health system, and families, unlike existing tools that mainly highlight the care team’s relationship with the mother. The CBVQ also considers the health system’s structures and family support, distinguishing it from other tools.